Comparing Digital Photography via Email Correspondence With Traditional Telephone Communication for Assessment of Postoperative Pediatric Urology Patients: A Pilot Randomized Controlled Trial. Issue 2 (April 2018) - Rickard, Mandy; Brownrigg, Natasha; Zizzo, Kevin; Lorenzo, Armando J.; DeMaria, Jorge; Braga, Luis H.
Abstract : Introduction: Postoperative concerns are commonly managed by a nurse practitioner (NP) via traditional telephone conversation (TTC). In recent years, electronic interaction, including digital photographs sent via email (PEC), has become an alternative, novel strategy to evaluate surgical site concerns. Its use may result in fewer unplanned clinic or emergency room (ER) visits as well as improve patient satisfaction. Herein, we present a pilot a study to determine the feasibility of conducting a definitive trial comparing the effectiveness of PEC versus TTC in reducing the number of unplanned clinic and ER visits as well as improving patient experience. Materials and Methods: Children < 18 years old at the time of surgery and within the 30-day postoperative period were recruited from June 2015 to January 2016 at a tertiary children's hospital. Exclusion criteria were concerns occurring outside the 30-day postoperative period and inability/unwillingness to email photographs. Patients were allocated to PEC or TTC after initiating contact with the NP through an electronic centralized blocked randomization system. A standardized telephone script was used to gather relevant clinical data for both groups. These data informed a clinical plan, with those randomized to the PEC group sending digital photographs of the surgical site in addition to the traditional telephone call. Within 48 hours, families were sent a link to an electronic survey measuring patient experience using a validated questionnaire. Feasibility data on recruitment rates, compliance with sending photographs, and completing patient experience questionnaires were collected. Secondary outcomes included number of unplanned clinic/ER visits, number of follow-up phone calls, and patient experience scores. Results: Of the 328 children who underwent urological procedures during the recruitment period, 215 (66%) consented to participate in the study. Of these, 42(13%) contacted the NP with postoperative concerns and were randomized. Two patients in the PEC group were excluded after randomization (one for contacting on Postoperative Day 31 and one for not sending photographs), resulting in 19 patients in the PEC group and 21 patients in the TTC group. Penile surgeries (hypospadias repair and circumcisions [43%]) were the most common procedures with postoperative concerns. Ninety-eight percent of the PEC patients were compliant in sending photographs. Overall, 98% of surveys were completed. Twice as many unplanned clinic visits were observed in the TTC group when compared with the PEC group ( p = .28), despite a similar number of follow-up phone calls between groups (Table 1). Patient experience scores were also comparable in both groups, with families scoring high satisfaction with the experience regardless of the modality of communication. Conclusions: A definitive trial examining the effectiveness of PEC versus TTC appears feasible and safe as seen by the high recruitment, photographic compliance, hospital visits, and survey completion rates in this pilot study.